Spelling predictors; investigating the role of phonological ability and rapid naming in a large cross-sectional British study. (August 2022) - Niolaki, Georgia; Vousden, Janet; Terzopoulos, Aris; Shepherd, Donna-Lyn; Debney, Lauren; Masterson, Jackie
Abstract: This study aimed to identify predictors of single word spelling performance in children using a novel test containing regular words, irregular words and pseudowords. We assessed reading ability, letter-sound knowledge, phonological awareness (PA) and rapid automatised naming (RAN) in children aged 4–12 years (N = 641). Mixed model analyses with hierarchical nested data were conducted with Year_group (Yr R to Yr 6) included as a factor, PA and RAN as predictors, and reading and letter-sound knowledge as covariates. For irregular word spelling, PA and RAN were significant predictors, but the associations were dependent upon the year the children attended. Interestingly, for regular words and pseudowords PA was not significantly related. For pseudowords, only RAN was a significant predictor and only in Yr 2. We argue that a better understanding of spelling development can be achieved using tools that distinguish between regular and irregular words and pseudowords, as different processes seem to be associated with the different types of letter string across the variable levels of spelling experience. Highlights: A novel spelling test containing regular and irregular words and pseudowords was used. The role of PA and RAN was explored with primary school spellers. For irregular word spelling, PA and RAN were significant predictors, but the associations were dependent upon the year the children attended. For regular words and pseudowords, PA was not significantly related. For pseudowords, only RAN was a significant predictor and only in Yr 2.